If I was a river - Arena, Tina; Afanasieff, Walter; Sony Music Entertainment (New York : Sony Music Entertainment, 1998)
Contains the single taken from the album In Deep.
CD 1 : If I Was A River (radio edit) / (4:07)
Koleksi Khas Wiramanja.
Title from the container.
Keywords: Songs, English